Development and Validation of a Precise and Stability Indicating LC Method for the Determination of Benzalkonium Chloride in Pharmaceutical Formulation Using an Experimental Design - Harshal K. Trivedi; Mukesh C. Patel (E-Journal of Chemistry)
A simple, precise, shorter runtime and stability indicating reverse-phase high performance liquid chromatographic method has been developed and validated for the quantification of benzalkonium chloride (BKC) preservative in pharmaceutical formulation of sparfloxacin eye drop. The method was successfully applied for determination of benzalkonium chloride in various ophthalmic formulations like latanoprost, timolol, dexametasone, gatifloxacin, norfloxacin, combination of moxifloxacin and dexamethasone, combination of nepthazoline HCl, zinc sulphate and chlorpheniramine maleate, combination of tobaramycin and dexamethasone, combination of phenylephrine HCl, naphazoline HCl, menthol and camphor. The RP-LC separation was achieved on an Purospher Star RP-18e 75 mm × 4.0 mm, 3.0 μ in the isocratic mode using buffer: acetonitrile (35: 65, v/v), as the mobile phase at a flow rate of 1.8 mL/min. The methods were performed at 215 nm; in LC method, quantification was achieved with PDA detection over the concentration range of 50 to 150 μg/mL. The method is effective to separate four homologs with good resolution in presence of excipients, sparfloxacin and degradable compound due to sparfloxacin and BKC within five minutes. The method was validated and the results were compared statistically. They were found to be simple, accurate, precise and specific. The proposed method was validated in terms of specificity, precision, recovery, solution stability, linearity and range. All the validation parameters were within the acceptance range and concordant to ICH guidelines.